Design and implementation of a triphasic energy and harmonics meter - Farfán Lira, José Enrique (2023)
This work presents the development of a device capable of measuring various parameters related to the tarification and quality of an electrical supply, in this case a 220V three-phase and 60Hz one, these are: the effective values and harmonics ​​of the voltages and currents of the system, together with their respective phase shifts, the systems frequency and the triphasic powers and energies (both active, reactive and apparent). This device is based on an ESP32 microcontroller programmed in C++ language which will be wirelessly connected to the web platform via Wi-Fi for remote reading. The external indicator for the measurement of active energy is through the pulsations of a led with a rate of 950 impulses/kw-h. In the case of harmonics measurement, the algorithm applies the fast Fourier transform, or FFT, on a representative wave period obtained by undersampling methods, or low-speed sampling, to increase the range of legible harmonics. The validation of the energy measurement is carried out by performing the contrast test detailed in IEC 62053-21, resulting in the class 1 and the validation of the others parameters meassurement is carried out by comparison with a network analyzer using the acceptance criteria of the IEC 61557-12 standard, also being class 1, both tests carried out in the electricity laboratory N°6 of the UNI.